2004
DOI: 10.1073/pnas.0305516101
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of the KaiC-interacting C-terminal domain of KaiA, a circadian clock protein: Implications for KaiA–KaiC interaction

Abstract: KaiA is a two-domain circadian clock protein in cyanobacteria, acting as the positive element in a feedback loop that sustains the oscillation. The structure of the N-terminal domain of KaiA is that of a pseudo-receiver, similar to those of bacterial response regulators, which likely interacts with components of the clock-resetting pathway. The C-terminal domain of KaiA is highly conserved among cyanobacteria and enhances the autokinase activity of KaiC. Here we present the NMR structure of the C-terminal doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 42 publications
(59 reference statements)
3
56
1
Order By: Relevance
“…We recently showed that KaiA is a two-domain protein with an N-terminal pseudo-receiver and a structurally novel, KaiCinteracting C-terminal domain (17,18). The C-terminal domain is sufficient to enhance the autokinase activity of KaiC in vitro, and we proposed (18) that protein-protein interactions at the N-terminal pseudo-receiver domain of KaiA function in signalinput to the clock.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that KaiA is a two-domain protein with an N-terminal pseudo-receiver and a structurally novel, KaiCinteracting C-terminal domain (17,18). The C-terminal domain is sufficient to enhance the autokinase activity of KaiC in vitro, and we proposed (18) that protein-protein interactions at the N-terminal pseudo-receiver domain of KaiA function in signalinput to the clock.…”
mentioning
confidence: 99%
“…In vitro studies show binding of KaiC to forked DNA (13); thus, KaiC has been proposed to interact directly with DNA in vivo and affect transcription levels by global chromatin remodeling (14). KaiC shares sequence similarity with the DnaB͞RecA bacterial helicase superfamily (15), and recent electron microscopy studies show that KaiC forms double ring-shaped hexameric particles in the presence of ATP or nonhydrolysable ATP analogs (13,16,17), with an Ϸ20-Å-diameter pore present at the center (13,17). KaiC has an autokinase activity as demonstrated in vitro (11,14,18) and in vivo (11,14,19).…”
mentioning
confidence: 99%
“…The three-dimensional structures of the proteins encoded by the kai genes have been determined (3,(5)(6)(7)(8)(9)(10). The Kai proteins interact with each other (11,12) to form large complexes in vivo in which KaiC is the core (13).…”
mentioning
confidence: 99%
“…With fitting élan, a small community of scientists has ripped open the packaging of the cyanobacterial circadian clock, compiled the parts list, examined the gears, and begun to piece together the mechanism. Over the past 2 years, the 3D molecular structures have been solved for the core components of the cyanobacterial circadian clock: KaiA, KaiB, and KaiC (1)(2)(3)(4)(5)(6). In a surprisingly literal analogy to mechanical timepieces, the protein that seems to be at the heart of the clock mechanism, KaiC, forms a hexameric ring that even looks like a cog: the escape wheel, perhaps (5,7,8).…”
Section: Center For Research On Biological Clocks Department Of Biolmentioning
confidence: 99%
“…Over the past 2 years, the 3D molecular structures have been solved for the core components of the cyanobacterial circadian clock: KaiA, KaiB, and KaiC (1)(2)(3)(4)(5)(6). In a surprisingly literal analogy to mechanical timepieces, the protein that seems to be at the heart of the clock mechanism, KaiC, forms a hexameric ring that even looks like a cog: the escape wheel, perhaps (5,7,8). Previous work has shown that KaiC has an autophosphorylation activity, and that the presence of KaiA and KaiB modulates the extent to which KaiC is phosphorylated (6,9).…”
Section: Center For Research On Biological Clocks Department Of Biolmentioning
confidence: 99%